2015
DOI: 10.1017/s0022215115000663
|View full text |Cite
|
Sign up to set email alerts
|

The utility of FloSeal haemostatic agent in the management of epistaxis

Abstract: Our findings suggest that FloSeal has a limited role in the management of epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Despite these promising results, the optimal first-line management of epistaxis remains debatable [ 21 ]. A randomized control trial directly comparing the efficacy of Floseal® (Baxter, USA) to traditional management for the control of persistent epistaxis in an OHNS patient population has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising results, the optimal first-line management of epistaxis remains debatable [ 21 ]. A randomized control trial directly comparing the efficacy of Floseal® (Baxter, USA) to traditional management for the control of persistent epistaxis in an OHNS patient population has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…7 Khan et al reported a comparison of outcomes of a series of 101 patients with epistaxis either treated with FloSeal or traditional epistaxis management techniques. 8 The reported overall success rate for FloSeal was 14%; successful in 66% of anterior epistaxis cases and in only 9% of posterior epistaxis cases. 8 This study supports our finding that FloSeal is less effective in controlling posterior epistaxis.…”
Section: Discussionmentioning
confidence: 96%
“…8 The reported overall success rate for FloSeal was 14%; successful in 66% of anterior epistaxis cases and in only 9% of posterior epistaxis cases. 8 This study supports our finding that FloSeal is less effective in controlling posterior epistaxis. Posterior epistaxis is generally more difficult to control, with a higher failure rate in nasal packing in terms of bleeding control.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is important to consider that rebleeding can result upon removal by causing mucosal abrasions or detaching eschar. 55 Some inflatable balloon packing (Rapid Rhino) is covered with hydrocolloid fabric to facilitate insertion and removal. In a prospective randomized controlled trial comparing polyvinyl acetate sponge and inflatable balloons with hydrocolloid fabric packs, the latter produced significantly lower scores for subjective patient discomfort during insertion and removal.…”
Section: Supporting Textmentioning
confidence: 99%